Disability prevention and rehabilitation: draft resolution presented by the delegations of Australia, Belgium, Canada, Chile, Denmark, Finland, Gambia, Ghana, Iceland, India, Indonesia, Jordan, Nicaragua, Norway, Sri Lanka, Swaziland, Sweden, Switzerland, Thailand, Tonga, Uganda, Union of Soviet Socialist Republics, Viet Nam and Zimbabwe - World Health Assembly, 42 (World Health Organization, 1989)
(Apenda item 18.2)